Analisis Kehamilan Resiko Empat Terlalu Pada Ibu Hamil Di Puskesmas Rajeg Tahun 2022 - Ismawati Ismawati; Tetin Rismayanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Background: The high MMR is caused by 4T, such as too many pregnancies, too young, too old, and too close to one another. Several factors that influence health behavior are knowledge, attitudes, family support, the role of health workers and the role of health cadres. The initial survey at the Rajeg Health Center in the period January-April 2022 from 240 mothers found 33 mothers (13.75%) who belonged to the 4T group.Objective: To find out the analysis of four-too-risk pregnancies in pregnant women at the Rajeg Health Center in 2022.Methods: This research is a quantitative analytic study with a cross sectional design. The sample in this study was K1 pregnant women who were in the area of the Rajeg Health Center July-September 2022 totaling 95 respondents with a total sampling technique. The research instrument used a questionnaire and an observation sheet. Data is primary data analyzed using chi square statistical test.Result: The results of the univariate analysis revealed that 34.7% of pregnant women with a risk of four too, had good knowledge of 53.7%, had a positive attitude of 56.8%, received 51.6% family support, the role of the midwife was good 58.9% and the role of the midwife was good. cadres less 55.8%. The results of the bivariate analysis showed that there was a significant relationship between knowledge (p = 0.000), attitudes (p = 0.014), family support (p = 0.000), the role of midwives (p = 0.000) and the role of cadres (p = 0.000) with pregnancy risk. four too in pregnant women